(untitled) (Bangladesh Journal of Neuroscience, 2013)
Background: Several studies have identified that low serum uric acid (UA) is a possible risk factor for Parkinson Disease (PD). The aim of my study was based on evaluation of association of serum uric acid with Parkinson Disease (PD). Objective: To evaluate the association of serum uric acid with Parkinson Disease(PD). Methodology: It was a case control study carried out in the Department of Neurology of Bangabandhu Sheikh Mujib Medical University. A total 50 patients of PD aged 45 years or above were taken as cases; and age and sex matched 50 healthy subjects or patients other than PD were taken as control. Serum UA levels were measured in both groups. Besides, any association was searched between serum UA with age, sex, duration and stage of PD, BMI and dietary habit. Results: The mean serum uric acid level in case group was 4.25±1.00 mg/dl and that of control group was 4.73±1.29 mg/dl. The mean serum uric acid in case group was statistically significant (p=0.038 which was <0.05) lower than that of control group. Serum UA levels gradually diminished as Hoehn & Yahr stage of PD increased. Also, disease duration of PD was found inversely related with serum UA. Male subjects in both case and control group had higher serum UA level than their female counter-part, but they had statistically significant higher UA in control group. In this study no correlation was found between age and BMI with serum UA in both case and control. Any association between serum UA and dietary habit was not found in this study because maximum subjects of this study used to take average protein diet. Conclusion: The aim of the study was to explore the association between serum uric acid with Parkinson Disease. The present study found statistically significant association between low serum uric acid with Parkinson Disease. Bangladesh Journal of Neuroscience 2013; Vol. 29 (2) : 115-123